Vasodilator effects of cromakalim and HA 1077 in diabetic rat aorta (Swiss Medical Weekly, 2012)
BACKGROUND: Impairment of the vasorelaxant responses have been reported in diabetes mellitus. In this study, the roles of the KATP channel and rho kinase pathway were evaluated by using the KATP channel opener cromakalim and Rho-kinase inhibitor HA 1077 in diabetic rat aorta. METHODS: Adult male Wistar rats weighing (250–300 g) were divided into diabetic and control groups. Diabetes was induced by a single intraperitoneal injection of streptozotocin (STZ, 55 mg/kg/i.p). RESULTS: Vasodilator responses induced by cromakalim (10–7 to 10–3M) and HA 1077 (10–6 to 10–4M) were significantly less in diabetic rings compared with control rings (p